SCIENTIFIC CAREER OF V.F. PIVOVAROV, A MEMBER OF THE RUSSIAN ACADEMY OF SCIENCES (RAS) - A. V. Soldatenko; O. N. Pishnaya; L. K. Gurkina (Овощи России)
On the 21th September of 2018 Pivovarov Victor Fedorovich – scientific adviser of the Federal Scientific Vegetable Center, Academician of Russian Academy of Sciences, Honored Scientist of Russian Federation, State Laureate of Science and Technology, Doctor of Agricultural Science, Professor, is celebrating 50 years of his scientific and pedagogical activity. Dr. Pivovarov V.F. is the leading scientist in the field of ecology, introduction, horticulture, breeding and seed production of vegetable crops. Since having been appointed to a director of VNIISSOK, V.F. Pivovarov has continued to keep up the best traditions of Russian plant breeding school. By now, the VNIISSOK has become a scientific and methodical center for vegetable plant breeding and seed production, where many theoretical studies, the advanced technologies and methods of development of initial breeding material of vegetable plants for further breeding programs are carried out.